Assessing patient safety implementation and its associate factors in a pediatric inpatient ward - Rukmini Rukmini; Siti Nur Qomariah; Eileen Savage (Universa Medicina, 2024)
Background Patient safety is an emerging healthcare discipline with the ultimate goal of reducing errors and harm to patients by implementing quality health services. The provision of patient safety is complex and difficult to achieve. The purpose of this research was to assess patient safety in hospital pediatric inpatient care and factors affecting nurses implementing pediatric patient safety.